2015
DOI: 10.1113/jp271182
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between retinal blood flow and arterial oxygen

Abstract: Key pointsr Vascular reactivity, the response of the vessels to a vasoactive stimulus such as hypoxia and hyperoxia, can be used to assess the vascular range of adjustment in which the vessels are able to compensate for changes in P O 2 .r Previous studies in the retina have not accurately quantified retinal vascular responses and precisely targeted multiple P aO 2 stimuli at the same time as controlling the level of carbon dioxide, thus precluding them from modelling the relationship between retinal blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 41 publications
3
49
0
Order By: Relevance
“…Decorrelation is not linearly related to blood velocity—laboratory measurements using the current OCTA system showed that the decorrelation-velocity curve begins to flatten around 2 millimeters per second and reaches saturation at approximately 6 millimeters per second. 44 Thus, the percentage reduction in flow index was expected to be smaller than the change in volumetric blood flow as measured by laser Doppler 11 or Doppler OCT techniques. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decorrelation is not linearly related to blood velocity—laboratory measurements using the current OCTA system showed that the decorrelation-velocity curve begins to flatten around 2 millimeters per second and reaches saturation at approximately 6 millimeters per second. 44 Thus, the percentage reduction in flow index was expected to be smaller than the change in volumetric blood flow as measured by laser Doppler 11 or Doppler OCT techniques. 19 …”
Section: Discussionmentioning
confidence: 99%
“…510 Physiologic variations in oxygen delivery to the retina were found to induce multiple hemodynamic changes. 11,12 The ability to characterize this response can be useful to investigate the retinal vascular physiology as well as pathophysiology of those diseases.…”
mentioning
confidence: 99%
“…The repeatability of these two techniques has been analysed under varying blood gas challenges and the results were previously reported (Cheng et al. ; Rose et al. ).…”
Section: Introductionmentioning
confidence: 88%
“…In contrast to the choroid, the retinal circulation does regulate in response to metabolic demand, and blood flow increases during hypoxia (Cheng et al, 2016; Eperon et al, 1975; Hickam and Frayser, 1966; Palkovits et al, 2014c; Wanek et al, 2013; Yi et al, 2015b). As a result, inner retinal PO 2 is quite resistant to hypoxia, which can be appreciated from Figure 12.…”
Section: Retinal Po2 In Hypoxia and Hyperoxiamentioning
confidence: 99%
“…The retinal circulation constricts during hyperoxia (Cheng et al, 2016; Gilmore et al, 2005; Grunwald et al, 1984a; Pournaras et al, 2008; Riva et al, 1986; Werkmeister et al, 2015). This tends to keep inner retinal PO 2 close to levels during air breathing, but the regulation is not perfect in cats, at least partly because the diffusion of O 2 from the choroid is unavoidable.…”
Section: Retinal Po2 In Hypoxia and Hyperoxiamentioning
confidence: 99%